A rare case of mucinous tubular and spindle cell renal cell carcinoma with sarcomatoid change - Maiti, Krishnendu; Roy, Pinaki; Datta, Chanda; Pal, Dilip Kumar (Indian Journal of Case Reports, 2018)
Mucinous tubular and spindle cell renal cell carcinoma is a rare and recently described subtype of RCC. We present the case ofa 45-year-old woman with incidentally detected left renal mass. Imaging revealed a large mass and left radical nephrectomy wasperformed, histopathology revealed it to be a mucinous tubular and spindle cell carcinoma with sarcomatoid change. She is underclose follow-up for the last 6 months.